Answer:
4
Step-by-step explanation:
36 = 9*h
9*h = 36
h = 36/9
h = 4
Answer:
4) 2
Step-by-step explanation:
(4-0) / (1-(-1)) = 4/2 = 2
(10-4) / (4-1) = 6/3 = 2
Answer:
learning only lang po yan
Step-by-step explanation:
meron ba kayong picture para makatulongan ako sayo
(2x^2 + 4x + 6) - (-3x - 5x^2 + 4)
The negative sign separating the expressions is just multiplying the rightmost expression by -1.
(2x^2 + 4x + 6) + (3x + 5x^2 - 4)
Now, let's add together terms that share the same variable.
2x^2 + 5x^2 = 7x^2
4x + 3x = 7x
6 + (-4) = 2
Let's combine each of these terms into one expression.
7x^2 + 7x + 2 is the final answer.
Answer:
Step-by-step explanation:
The concept of binomial probability is applied.
Mathematically from binomial probability ; (nCx)px(1−p)(n-x)
The detailed step by step is as shown in the attachment